Photophysiological responses of marine diatoms to elevated CO2 and decreased pH: a review - Gao, Kunshan; Campbell, Douglas A.; 高坤山 (CSIRO PUBLISHING, 2014)
Diatoms dominate nearly half of current oceanic productivity, so their responses to ocean acidification are of general concern regarding future oceanic carbon sequestration. Community, mesocosm and laboratory studies show a range of diatom growth and photophysiological responses to increasing pCO(2). Nearly 20 studies on effects of elevated pCO(2) on diatoms have shown stimulations, no effects or inhibitions of growth rates. These differential responses could result from differences in experimental setups, cell densities, levels of light and temperature, but also from taxon-specific physiology. Generally, ocean acidification treatments of lowered pH with elevated CO2 stimulate diatom growth under low to moderate levels of light, but lead to growth inhibition when combined with excess light. Additionally, diatom cell sizes and their co-varying metabolic rates can influence responses to increasing pCO(2) and decreasing pH, although cell size effects are confounded with taxonomic specificities in cell structures and metabolism. Here we summarise known diatom growth and photophysiological responses to increasing pCO(2) and decreasing pH, and discuss some reasons for the diverse responses observed across studies.